Analisis Peran Etnofarmasi Sambai Oen Peugaga dalam Tradisi Ramadhan: Refleksi Kearifan Lokal Aceh - Ardhana Yulisma; Fadhiliana Nur Aprilia (Jurnal Serambi Engineering, 2025)
Sambai oen peugaga is a traditional Acehnese dish closely associated with the month of Ramadan and contains more than 40 types of local medicinal plants. This dish serves not only as a complementary culinary delight but also holds significant ethnopharmacological value. This study aims to analyze the role of sambai oen peugaga in supporting health during fasting as well as to explore the underlying local wisdom values. The method employed is a qualitative descriptive approach through a literature review of various scientific and cultural sources. The findings indicate that most plants used in sambai oen peugaga contain active compounds such as flavonoids, saponins, curcuminoids, and essential oils, which exhibit anti-inflammatory, antioxidant, immunostimulant, and antimicrobial effects. The combination of these compounds supports digestive health, immune function, and reduces oxidative stress during fasting. From a socio-cultural perspective, sambai oen peugaga functions as a medium for transmitting values, strengthening family cohesion, and reflecting a harmonious relationship between humans and nature. These findings underscore the importance of preserving traditional plant-based culinary heritage as part of community health systems and open opportunities for developing locally competitive functional food products.